The Main Purpose of Islamic Sharia in Environmental Conservation - La Ode Angga (Indonesian Journal of Built Environmental and Sustainability, 2020)
In the perspective of Islamic law (read: Jurisprudence), the preservation of the earth and human responsibility for nature and the environment, actually has long been discussed. Efforts to develop the fiqh of the earth and formulate it into more systematic and practical frameworks need to be worked on immediately. Classic fiqh content that discusses environmental themes separately and abstractly needs to be given ecological weight. For example, discussions in classical Jurisprudence books, such as the chapter taharah (purification), shaid (hunting), ihya 'al-mawat (utilizing dead land), al-'at`imah (law on food), sharibah (law on drinks), etc. From here, fiqh of the earth can be an entry point towards strengthening the role's capacity. Not only to protect the earth, jurisprudence of the earth also has a role to sustain the global movement on the issue of sustainable nature conservation. In this context, fiqh of the earth can be the vanguard for strengthening the capacity of Islamic law in modern life.In this case, there are several values that must be guided as a practical basis in formulating and developing fiqh of the earth, including: a. The creation of the universe including the environment of the human cosmos (land, water and air) has determined qadar (size or stipulation) which must always be maintained and preserved. So whoever destroys it means that it has corrupted the qadar of Allah. This is as confirmed in the Surah al-Hijr verse: 19-20: "And We have spread the earth and made it into the mountains and We have grown everything according to size. And we have made for you on earth the necessities of life, and (We also create) creatures that you are not a beneficiary of. b. All actions that damage the balance and preservation of the earth and nature are basically a violation of religion and sin. In Surah al-A'raf: 56, ALLAH SWT said: "Do not make mischief on earth (the world) after being reformed, pray to Him with fear and longing; God's grace is always close to those who do good. " The phrase "do not do damage on earth after being reformed" (wa lâ tufsidû fii al-ardl ba'da ishlâhih) - in surah al-A'raf verse 56 above - contains a double meaning. First, the prohibition to damage the earth after repairing (ishlah), which is when the earth was created by ALLAH SWT. This meaning shows the task of humans to protect the earth which is already a good place for human life.